2023
DOI: 10.1021/acsami.2c16720
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating a Partially Fluorinated Hybrid Cation-Exchange Membrane for Long Durable Performance of Vanadium Redox Flow Batteries

Abstract: The long-term durability of vanadium redox flow batteries (VRFBs) depends on the stability and performance of the membrane separator. We have architected a hybrid membrane by uniform dispersion of MIL-101(Cr) (Cr-MOF) in a partially fluorinated polymer grafted with sulfonic acid groups (PHP@AMPS Cr-MOF(1.0) ). The single cell VRFB performance of the PHP@AMPS Cr-MOF(1.0) membrane was studied in comparison with the Cr-MOF incorporated Nafion membrane (Nafion Cr-MOF(1.0) ) and showed an excellent result with 97.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…PHP@AMPS Cr-MOF(1.0) composite membrane's battery performance exhibited a splendid Coulombic efficiency (CE) (97.5%) at 150 mA cm −2 . 17 Recently, a study demonstrated that Zr-based MOFs have outstanding acid stability and oxidative stability, especially MOF-801 and MOF-808. Xin et al introduced MOF-801 and MOF-808 into SPEEK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHP@AMPS Cr-MOF(1.0) composite membrane's battery performance exhibited a splendid Coulombic efficiency (CE) (97.5%) at 150 mA cm −2 . 17 Recently, a study demonstrated that Zr-based MOFs have outstanding acid stability and oxidative stability, especially MOF-801 and MOF-808. Xin et al introduced MOF-801 and MOF-808 into SPEEK.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma and Shahi designed a composite membrane by evenly dispersing MIL-101­(Cr) within a polymer that was functionalized with sulfonic acid groups (PHP@AMPS Cr‑MOF(1.0) ). PHP@AMPS Cr‑MOF(1.0) composite membrane’s battery performance exhibited a splendid Coulombic efficiency (CE) (97.5%) at 150 mA cm –2 . Recently, a study demonstrated that Zr-based MOFs have outstanding acid stability and oxidative stability, especially MOF-801 and MOF-808.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium flow battery (VFB), as a promising candidate for large-scale energy storage/conversion system, has been regarded as a solution to the intermittency and volatility of renewable resources. VFB has numerous merits, including long cycle life, safety, and independently scalable power and capacity. As a key component, the membrane mainly plays two roles: (i) to separate the positive and negative electrolytes of VFB and (ii) to allow protons to transfer to form an internal circuit and obstruct the cross-migration of vanadium ions. An ideal membrane should have excellent proton conductance and strong vanadium ions resistance and stability. , …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] The cationic exchange side chains have been widely investigated (as in Naon membranes), aiming to fabricate nano-scale wide ion conductive channels for fast proton conduction; however, they usually suffer from low coulomb efficiency and capacity retention. 21,22 To avoid high vanadium permeation through the anionic wide channels, one strategy is the hydrophilic non-ionic side chain that narrows the ion conductive channels via the less dissociated hydroxyl group 18 and amino group; 16 another strategy is the amphiprotic side chain that introduces cationic Donnan effect to the ion conductive membranes. 12,23 Despite the advantages, the-state-of-the-art non-ionic and amphiprotic side chains oen suffer from relatively high proton conduction resistance, difficulty in tuning the ratio of the anionic to cationic groups, being easy to precipitate by ionic cross-linking, etc., which restrict the balance between energy efficiency and capacity retention.…”
Section: Introductionmentioning
confidence: 99%